1996
DOI: 10.1111/j.1751-1097.1996.tb02994.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Correspondence between Spore Dosimetry and Spectral Photometry of Solar Ultraviolet Radiation

Abstract: The biologically effective dose of solar UV radiation was estimated from the inactivation of UV-sensitive Bacillus subtilis spores. Two types of independent measurements were carried out concurrently at the Aerological Observatory in Tsukuba: one was the direct measurement of colony-forming survival that provided the inactivation dose per minute (ID/min) and the other was the measurement of the spectral irradiance by a Brewer spectrophotometer. To obtain the effective spectrum, the irradiance for each 1 nm wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 14 publications
1
28
0
2
Order By: Relevance
“…Using a series of cutoff filters, two independent studies have concluded that the most effective portion of the solar spectrum for inactivation of spore dosimeters consisted of UV-B radiation in the 305-to 325-nm range (117,217). A recent experiment simultaneously compared the response of the spore dosimeter with that of a Brewer sunlight spectrophotometer at the same location and over the same time periods and found good correlation between the two methods, indicating that the spore dosimetric system was indeed a relevant method for monitoring biologically active solar UV (123).…”
Section: B Subtilis Spores As Biological Solar Dosimetersmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a series of cutoff filters, two independent studies have concluded that the most effective portion of the solar spectrum for inactivation of spore dosimeters consisted of UV-B radiation in the 305-to 325-nm range (117,217). A recent experiment simultaneously compared the response of the spore dosimeter with that of a Brewer sunlight spectrophotometer at the same location and over the same time periods and found good correlation between the two methods, indicating that the spore dosimetric system was indeed a relevant method for monitoring biologically active solar UV (123).…”
Section: B Subtilis Spores As Biological Solar Dosimetersmentioning
confidence: 99%
“…An increased UV-B level of solar radiation will have many harmful effects on the biosphere and on human health (229). A quantitative assessment of the implications of progressive ozone depletion for life on Earth has been attempted theoretically, by applying radiative transfer models for different total ozone columns, where the resulting solar spectrum is weighted with biological action spectra (96), or attempting to correlate the inactivation rate of biological dosimeters exposed to sunlight with simultaneous measurements of ozone column thickness and spectral irradiance (120,123,159), or experimentally by applying UV radiation suitable for the simulation of a certain degree of ozone depletion (14). Solar UV dosimetry based on spore inactivation is probably the most sensitive measure of the change in the ozone concentration because of the high relative sensitivity to the shorter-wavelength portion of solar spectrum.…”
Section: Monitoring the Ozone Layer With Spore Dosimetersmentioning
confidence: 99%
“…A Japanese group found a good correlation between spectral irradiance of solar irradiation and the inactivation of UV-sensitive Bacillus subtilis spores (TKJ6321) [34,35]. The spores had been ®xed on a membrane and attached to a slide mount or cardboard to measure ambient UV radiation and personal UV exposure [36].…”
Section: Introductionmentioning
confidence: 99%
“…O dosímetro de esporos tem sido preparado no Laboratório de Ciência da Vida da Faculdade de Ciências da Universidade Rikkyo, Tóquio, Japão, onde os esporos da cepa mutante de Bacillus subtilis TKJ6312 são misturados com 0,6% (m/v) de agarose. 15 Quatro alíquotas de 5 µL dessa suspensão, cada uma contendo aproximadamente 10 6 esporos são adicionadas sobre um filtro de membrana e dispostos em slides. Em seguida, uma amostra é coberta com cartão (controle).…”
Section: Introductionunclassified